Brain arteriovenous malformation in hereditary hemorrhagic telangiectasia: Recent advances in cellular and molecular mechanisms - Drapé, Elise; Anquetil, Typhaine; Larrivée, Bruno; Dubrac, Alexandre (Frontiers in Human Neuroscience, 2022)
Hereditary hemorrhagic telangiectasia (HHT) is a genetic disorder characterized by vessel dilatation, such as telangiectasia in skin and mucosa and arteriovenous malformations (AVM) in internal organs such as the gastrointestinal tract, lungs, and brain. AVMs are fragile and tortuous vascular anomalies that directly connect arteries and veins, bypassing healthy capillaries. Mutations in transforming growth factor β (TGFβ) signaling pathway components, such as ENG (ENDOGLIN), ACVRL1 (ALK1), and SMAD4 (SMAD4) genes, account for most of HHT cases. 10–20% of HHT patients develop brain AVMs (bAVMs), which can lead to vessel wall rupture and intracranial hemorrhages. Though the main mutations are known, mechanisms leading to AVM formation are unclear, partially due to lack of animal models. Recent mouse models allowed significant advances in our understanding of AVMs. Endothelial-specific deletion of either Acvrl1, Eng or Smad4 is sufficient to induce AVMs, identifying endothelial cells (ECs) as primary targets of BMP signaling to promote vascular integrity. Loss of ALK1/ENG/SMAD4 signaling is associated with NOTCH signaling defects and abnormal arteriovenous EC differentiation. Moreover, cumulative evidence suggests that AVMs originate from venous ECs with defective flow-migration coupling and excessive proliferation. Mutant ECs show an increase of PI3K/AKT signaling and inhibitors of this signaling pathway rescue AVMs in HHT mouse models, revealing new therapeutic avenues. In this review, we will summarize recent advances and current knowledge of mechanisms controlling the pathogenesis of bAVMs, and discuss unresolved questions.